Deficiency in the Screening Process of Fabry Disease: Analysis of Chronic Kidney Patients Not on Dialysis - Battaglia, Yuri; Fiorini, Fulvio; Azzini, Cristiano; Esposito, Pasquale; De vito, Alessandro; Granata, Antonio; Storari, Alda; Mignani, Renzo (Frontiers in Medicine, 2021)
Fabry Disease (FD), a rare and progressive, X-linked lysosomal storage disorder, is caused by mutations in the α-galactosidase A (GLA) gene which leads to enzymatic deficiency of GLA. Misdiagnosed and undiagnosed FD cases are common for the variable FD phenotype, ranging from asymptomatic and/or impairment of single organs, which is typically seen in females and in patients with late-onset mutation, to multiple organ disease, which is frequently found in males with classic GLA mutation. Consequently, for an early diagnosis and an efficient treatment of FD, three different strategies of screening, new-born screening, high-risk screening and familiar screening, have been conducted. However, most of FD screening in the CKD population has been carried out in hemodialysis patients and kidney transplant recipients, for whom the renal damage is already irreversible, so the effectiveness of enzymatic replacement therapy is limited and delayed therapeutic intervention results in worse long-term outcomes. This review investigates the actual strategies of screening initiatives for the identification of FD, examining in detail those performed in CKD patients not on dialysis.